Symptoms and Critical Illness Among Obstetric Patients With Coronavirus Disease 2019 (COVID-19) Infection. Issue 2 (August 2020) - Andrikopoulou, Maria; Madden, Nigel; Wen, Timothy; Aubey, Janice J.; Aziz, Aleha; Baptiste, Caitlin D.; Breslin, Noelle; D'Alton, Mary E.; Fuchs, Karin M.; Goffman, Dena; Gyamfi-Bannerman, Cynthia; Matseoane-Peterssen, Dara N.; et al.
Abstract : OBJECTIVE: To characterize symptoms and disease severity among pregnant women with coronavirus disease 2019 (COVID-19) infection, along with laboratory findings, imaging, and clinical outcomes. METHODS: Pregnant women with COVID-19 infection were identified at two affiliated hospitals in New York City from March 13 to April 19, 2020, for this case series study. Women were diagnosed with COVID-19 infection based on either universal testing on admission or testing because of COVID-19–related symptoms. Disease was classified as either 1) asymptomatic or mild or 2) moderate or severe based on dyspnea, tachypnea, or hypoxia. Clinical and demographic risk factors for moderate or severe disease were analyzed and calculated as odds ratios (ORs) with 95% CIs. Laboratory findings and associated symptoms were compared between those with mild or asymptomatic and moderate or severe disease. The clinical courses and associated complications of women hospitalized with moderate and severe disease are described. RESULTS: Of 158 pregnant women with COVID-19 infection, 124 (78%) had mild or asymptomatic disease and 34 (22%) had moderate or severe disease. Of 15 hospitalized women with moderate or severe disease, 10 received respiratory support with supplemental oxygen and one required intubation. Women with moderate or severe disease had a higher likelihood of having an underlying medical comorbidity (50% vs 27%, OR 2.76, 95% CI 1.26−6.02). Asthma was more common among those with moderate or severe disease (24% vs 8%, OR 3.51, 95% CI 1.26−9.75). Women with moderate or severe disease were significantly more likely to have leukopenia and elevated aspartate transaminase and ferritin. Women with moderate or severe disease were at significantly higher risk for cough and chest pain and pressure. Nine women received ICU or step-down–level care, including four for 9 days or longer. Two women underwent preterm delivery because their clinical status deteriorated. CONCLUSION: One in five pregnant women who contracted COVID-19 infection developed moderate or severe disease, including a small proportion with prolonged critical illness who received ICU or step-down–level care. Abstract : One in five pregnant women who contract coronavirus disease 2019 (COVID-19) infection will develop moderate or severe disease.